Bioprospection of Enggano Macroscopic Fungi as Antibacterial and Antioxidant Agents - Evana Evana; Kartika Dyah Palupi; Listiana Oktavia; Ahmad Fathoni (Research Center for Biology-Indonesian Institute of Sciences, 2021)
Macrofungi in Indonesia have not been widely studied for their pharmacological activity, especially as a source of antibacterial and antioxidant properties, even though Indonesia as a tropical country has quite a high diversity of macrofungi. This study aims to reveal the potential of macrofungi from the Enggano forest as a source of antibacterial and antioxidant compounds. Four types of macrofungi were collected and their metabolites were extracted using four types of organic solvents. Antibacterial and antioxidant activity assay of the extract was carried out using the TLC Bioautography method. From the sixteen macrofungal extracts, there is one extract that has the strongest antibacterial activity compared to the others, namely n-hexane Coriolopsis polyzona. It showed moderate antibacterial activity against Staphylococcus aureus and Escherichia coli with MIC values of 256–128 μg/mL, respectively. Meanwhile, the antioxidant activity of the macrofungal extracts showed weak activity with IC50 values of 3080–7370 μg/mL (AAI values of 0.033–0.079).